Quality of life of high-functioning children with autism spectrum disorders, aged between 8–17 years - Ólafsdóttir, Linda Björk; Egilson, Snæfríður Þóra; Ólafsson, Kjartan (Icelandic Journal of Education, 2015)
Objectives: This study focused on the quality of life (QoL) of high-functioning children with autism spectrum disorders (ASD), aged 8–17 years. The purpose of the study was twofold; firstly to explore how high-functioning children with ASD experience their quality of life compared to peers in a control group. Secondly to explore how parents evaluate their children’s QoL. The study is part of a larger project named Quality of life, participation and environment of children living in Iceland which is implemented in cooperation with the State Diagnostic and Counselling Center.Method: A cross-sectional descriptive comparative design was used in the study. Data was collected with the Icelandic version of the KIDSCREEN-27, a generic quality of life questionnaire for use with children and adolescents. KIDSCREEN-27 measures five QoL dimensions: Physical Well-being (5 items), Psychological Well-being (7 items), Parent Relations & Autonomy (7 items), Social Support & Peers (4 items), and School (4 items). A total of 109 children with ASD and 129 parents of children with ASD answered the questionnaire as well as 251 children and 286 parents in a control group. Independent t-tests were conducted to compare group differences. Mixed between-within subjects ANOVA was used to relate QoL to background information on the children and their families. Reliability was assessed using Cronbach’s alpha.Findings: Overall, high-functioning children with ASD were positive towards their position in life although some difficulties existed. On the KIDSCREEN-27 the children evaluated their QoL within half a standard deviation from the average normal distribution on all five QoL dimensions. The lowest scores were within the dimensions Physical Well-being and Social Support & Peers where the children’s QoL was on the verge of being less than average. Furthermore, children with ASD evaluated their QoL to be significantly less than their peers in the control group on all dimensions. The parents of high-functioning children with ASD ...